Word Sense Disambiguation: A Survey (International Journal of Engineering and Computer Science, 2015)
Word sense disambiguation is the name of the process of assigning proper sense to a word having the potentiality of multiple senses in an automatic computational platform such as computational linguistics. It is one of the well discussed problems of natural language processing. The process involves a lot of difficulty due to lack of reasoning power and commonsense of computers. So human has to formalize some algorithms to computerize the process of sensing the appropriate sense of a word within a given context. This is the main aim of WSD approaches. During this survey, we have basically discussed about different approaches and also implementations of these approaches in different languages like Chinese, Japanese and also in Indian languages like Hindi, Nepali and Tamil.